Dialektika Nalar dan Riwayat dalam Tafsir Jami’ al-Bayân ‘an Ta’wil al-Quran Karya Imam Ath-Thabari - Kalbajapen (Journal of Society and Scientific Studies, 2026)
Although the literature places Tafsir ath-Thabari at the highest rank of the bi al-ma'tsur category due to its abundance of sanad, this absolute labeling sparks epistemological debate. Ath-Thabari's activities are not passive, but actively integrate sharp reasoning, linguistic analysis, and independent ijtihad to filter and interpret history. This qualitative literature research with a dialectical-analytical approach (tahlili) aims to explain the dynamic dialectical space between reason ('aql) and text (naql), in order to prove that reason is the main methodological instrument, not just a complement. Primary data comes from Tafsir Jami' al-Bayan, while tafsir methodology literature and intellectual biography are secondary data. Data collection uses documentation techniques and critical reading (close reading) of verses with contradictory histories. The research results found that the Tafsir bi al-Ma'tsur label on this work is only superficial. Substantially, this book is a dynamic, symbiotic and integrative dialectical space between the authority of the text and the sharpness of reason. Ath-Thabari positions history as the main foundation that is tested critically through sanad selection, mature criticism based on the principle of 'ishmatul anbiya, and classification of history. The reasoning portion (ra'yu) works predominantly as an analytical tool through the rules of al-tarjih ushuliyah, Arabic grammatical-semantic analysis of Jahiliah poetry, as well as independent legal istinbath as Mujtahid Mutlaq. This relationship between reason and history complements each other to produce interpretations that are beneficial, scientific and universal.